CONCENTRATION OF STUDENT’S LEARNING THROUGH UTILIZATION OF QUIZLET APPLICATION ON LEARNING EVALUATION - Sihotang, Hotmaulina; Harefa, Nelius; Lamsari, Leony Sangat; Murniarti, Erni (Advances in Social Sciences Research Journal, 2021)
Concentration of student’s learning is an important variable that can affect cognitive, affective, psychomotor, and students’ scientific process skills. In efforts to improve the concentration of student’s learning can be done by applying models, media, and learning strategies. In the study, interpretation and analysis of data increases the concentration of student learning by utilizing learning media based on the Quizlet application. Data of interpretation and analysis has showed that there was an increase in the concentration of student learning by using the Quizlet application in indicator of the attention gains value of 0.78 in the high category, an indicator of understanding with 0.77 in the high category, an indicator of activeness with 0.77 in the high category, accuracy indicators with 0.76 in the high category, and indicators of calm with 0.78 also in the high category. Thus, based on the interpretation of the values, it concludes that the application of Quizlet has the capability to improve the concentration of student’s learning. The highest increase in learning concentration with the use of the Quizlet application as indicators of attention and calm gains value of 0.78 in the high category. On the contrary, the lowest increase in learning concentration with the use of the Quizlet application on accuracy indicators with a gain value of 0.76 in the high category. Based on the interpretation and analysis of the value of each indicator gain, it is concluded that the application of Quizlet can improve student learning concentration